THE CRYSTAL STRUCTURE OF ALLOCHALCOSELITE, Cu+Cu2+ 5PbO2(SeO3)2Cl5, A MINERAL WITH WELL-DEFINED Cu+ AND Cu2+ POSITIONS - Krivovichev S.V.; Filatov S.K.; Burns P.C.; Vergasova L.P. (My University, 2006)
The crystal structure of allochalcoselite, Cu+Cu2+5PbO2(SeO3)2Cl5, a new mineral species from the fumaroles of the Great Tolbachik fissure eruption, in the Kamchatka Peninsula, Russia, has been solved from single-crystal X-ray-diffraction data by direct methods and refined to R1 = 0.047 for 1235 unique reflections with |Fo| ≥ 4sF. The mineral is monoclinic, space group C2/m, a 18.468(2), b 6.1475(8), c 15.314(2) Å, b 119.284(2) o, V 1516.5(3) Å3, Z = 4. The structure contains one symmetrically unique Pb position coordinated by three O and four Cl atoms. There are two Se4+ cations, which form SeO3 trigonal pyramids. There are six symmetrically independent Cu sites in allochalcoselite, four of which [Cu1–Cu4] are occupied by Cu2+ and two [Cu5 and Cu6] by Cu+ cations. The Cu1, Cu2, and Cu3 sites have distorted octahedral [4O + 2Cl], [(3O + Cl) + 2Cl], and [(3O+ Cl) + 2Cl] coordinations, respectively. The Cu4 site forms a trigonal CuO3Cl2 bipyramid with one equatorial and one apical vertex occupied by Cl. The Cu+ cations are both coordinated by two Cl – anions to form linear anions [Cu+Cl2] –, with Cl–Cu–Cl angles of 180°. The structure can be appropriately described in terms of arrangements of the strong M–O bonds (M = Se4+, Cu2+ and Pb2+). These bonds are accumulated within layers parallel to (100), with some of the Cl – anions sandwiched between them. The O4 and O5 atoms are not bonded to Se4+ cations, and are tetrahedrally coordinated by four metal atoms. The [O4PbCu3] 6+ and [O5Cu4]6+ tetrahedra are linked via Cu1 atoms into [O2Cu5Pb]8+ chains extending parallel to the b axis. The [SeO3]2– pyramids are attached to oxocentered tetrahedra in “face-to-face” positions to form complex ([O2Cu5Pb][SeO3]2)4+ chains that are linked together to form a metal–oxygen layer parallel to (100). The layer has large pores that are occupied by the [Cu+Cl2] – anions. These anions are held in the structure via weak Cu2+–Cl – bonds (> 2.8 Å) only. Thus allochalcoselite can be considered as a kind of delicately balanced host–guest system with [Cu+Cl2] – anions included into the Cu2+ oxoselenite chloride matrix. Relatively isolated and weakly bonded positions of the [Cu+Cl2] – anions in the structure may indicate stability of these complexes as separate entities and their possible role in the Cu+ transport by volcanic gases.
Keywords: allochalcoselite; crystal structure; copper; selenite; Tolbachik volcano; Russia